CGIAR Core Metadata Schema version 2 - CGIAR Platform for Big Data in Agriculture (2020)
The Core metadata schema version 2 is an improved version of the version 1 created by the CGIAR Metadata Working Group. This version 2 was approved by all members of the working group and is published as a GitHub repo, ready for uptake.